Major reductions in unnecessary aspartate aminotransferase and blood urea nitrogen tests with a quality improvement initiative. Issue 10 (9th May 2019) - Strauss, Rachel; Cressman, Alex; Cheung, Mark; Weinerman, Adina; Waldman, Suzanne; Etchells, Edward; Zahirieh, Alireza; Tartaro, Piero; Rezmovitz, Jeremy; Callum, Jeannie
Abstract : Background/context: Unnecessary laboratory testing leads to considerable healthcare costs. Aspartate aminotransferase (AST), commonly ordered with alanine aminotransferase (ALT) and blood urea nitrogen (BUN), commonly ordered with creatinine (Cr), often add little value to patient management at significant cost. We undertook a choosing wisely based quality improvement initiative to reduce the frequency of testing. Objectives: To reduce the ratio of AST/ALT and BUN/Cr to less than 5% for all inpatient and outpatient test orders. Measures: Absolute number and ratio of AST/ALT and BUN/Cr; AST, ALT, BUN and Cr tests per 100 hospital days; projected annualised cost savings and monthly acute inpatient bed days. Improvements: We created guidelines for appropriate indications of AST and BUN testing, provided education with audit and feedback and removed AST and BUN from institutional order sets. Impact/results: The ratios of AST/ALT and BUN/Cr decreased significantly over the study period (0.37 to 0.14, 0.57 to 0.14, respectively), although the goal of 0.05 was not achieved due to a delay in adopting the choosing wisely strategies during the study time period by some inpatient units. The number of tests per 100 hospital days decreased from 20 to 7 AST (95% CI 19 to 20.5, 5.6 to 8.7, p<0.001) and from 72 to 17 BUN (95% CI 70 to 73.4, 16.6 to 22.9, p<0.001). The initiative resulted in a projected annualised cost savings of C$221 749. Discussion: A significant decrease in the AST/ALT and BUN/Cr ratios can be achieved with a multimodal approach and will result in substantial healthcare savings.